Assessing flood risks and the coping strategy: a community adaptation in floodplain areas at Beaufort district in East Malaysia - Jafar Adi; Sakke Nordin; Mapa Mohammad Tahir; Dollah Ramli; Joko Eko Prayitno (World Research Association, 2022)
Floodplains have become increasingly populated areas throughout Malaysia as shown in the case of Beaufort district situated in the state of Sabah at East Malaysia. This area is now exposed to flood hazards due to the rise of new settlements. Nonetheless, the commpunity in the district has managed to survive and thrive with the prevalence of flood hazards. The aim of this study is to identify the risk of loss level faced by affected communities in the area as well as the coping strategies practised during floods. A survey consisting of 241 heads of households in four villages was conducted in Beaufort. The raw data was analysed using the chisquare, mean score and frequency. The study outcomes reveal that there are various risks of loss present in all villages such as the risk of death (RD), the risk of injury (RI), the risk of property loss (RPL) and the risk of loss of home infrastructure (RLSI).